Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Get detailed answers to your questions from a community of experts dedicated to providing accurate information. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
Answer:
[tex]y = -2x +7[/tex]
Step-by-step explanation:
Given
[tex](x_1,y_1) = (-3,13)[/tex]
[tex](x_2,y_2) = (6,-5)[/tex]
Required
Determine the equation in slope intercept form
First, we calculate the slope:
[tex]m = \frac{y_2 - y_1}{x_2 - x_1}[/tex]
The equation becomes:
[tex]m = \frac{-5 - 13}{6 - (-3)}[/tex]
[tex]m = \frac{-5 - 13}{6 +3}[/tex]
[tex]m = \frac{-18}{9}[/tex]
[tex]m = -2[/tex]
The equation is then calculated using:
[tex]y -y_1 = m(x - x_1)[/tex]
Substitute values for y1, m and x1
[tex]y - 13 = -2(x -(-3))[/tex]
[tex]y - 13 = -2(x +3)[/tex]
[tex]y - 13 = -2x -6[/tex]
Make y the subject
[tex]y = -2x - 6 + 13[/tex]
[tex]y = -2x +7[/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.